Enhanced lindane removal from soil slurry by immobilized Streptomyces consortium - Sáez, Juliana María (2014)
Lindane is a chlorinated insecticide which was used worldwide. Nowadays its persistence, bioaccumulation and toxicity are well known. One of the strategies for its elimination is bioremediation. For this purpose, the use of slurry reactors for contaminated soils is considered an efficient technology. Moreover, using immobilized cells in this process could provide protection for microorganisms against the contaminants and also allows reuse. The aim of this study was to assess lindane removal from soil slurry by a Streptomyces consortium immobilized in cloth sachets, at different inoculum, lindane and slurry concentrations. In concentrated slurry, the higher lindane removal (35.3 mg Kg-1) was obtained with the medium inoculum (107 CFU g-1) and the higher lindane concentration tested, at 7 days of incubation. Although, lindane removal was also detected in abiotic controls, probably due to a physical phenomenon of adsorption of the pesticide to soil particles. Thus, these parameters were selected for evaluating the pesticide removal in a more diluted slurry. After 14 days of incubation, 28.7 mg Kg-1 of lindane was removed. Besides, phytotoxicity assay demonstrated that seeds grown on diluted slurries bioremediated during 7 and 14 days showed an improvement in biological paramethers, respect to non-bioremediated slurry.